The symmetric tridiagonal eigenproblem on a shared memory multiprocessor: Part II - Kaya, D (Elsevier Science Inc, 2005)
The article presents an experimental evaluation of the effect of deflation on accuracy. A number of test matrices were used to test Cuppen's algorithm since the amount of deflation in this method depends oil the test matrix. The motivation for a non-recursive version was to compare this with the recursive version and to investigate the relationship between the recursive and non-recursive implementations of Cuppen's divide-andconquer method. Empirical comparison was carried Out using C++ and the THREADS package on a shared memory Encore Multimax multiprocessor. The algorithms illustrate the advantages of parallel algorithms using dynamic allocation of tasks to THREADs on this shared memory machine. (C) 2004 Elsevier Inc. All rights reserved.
Keywords: the symmetric tridiagonal eigenproblem; Cuppen's rnethod; parallel computation; a shared memory Encore Multimax multiprocessor